SOME REMARKS ON GENERALIZED SEQUENCE SPACE OF BOUNDED VARIATION OF SEQUENCES OF FUZZY NUMBERS - Altinok, H.; Et, M.; Colak, R. (Univ Sistan & Baluchestan, 2014)
The idea of difference sequences of real (or complex) numbers was introduced by Kizmaz [8]. In this paper, using the difference operator and a lacunary sequence, we introduce and examine the class of sequence b upsilon(theta) (Delta, F) We study some of its properties like solidity, symmetricity, etc.
Keywords: Fuzzy number; Difference operator; Lacunary sequence